A gene regulatory network controlled by the NAC transcription factor ANAC092/AtNAC2/ORE1 during salt-promoted senescence - Balazadeh, Salma (2010)
Onset and progression of senescence are under genetic and environmental control. The Arabidopsis thaliana NAC transcription factor ANAC092 (also called AtNAC2 and ORE1) has recently been shown to control age-dependent senescence, but its mode of action has not been analyzed yet. To explore the regulatory network administered by ANAC092 we performed microarray-based expression profiling using estradiol-inducible ANAC092 overexpression lines. Approximately 39% of the 170 genes up-regulated upon ANAC092 induction are known senescence-associated genes, suggesting the NAC factor exerts its role in senescence through a regulatory network that includes many of the genes previously reported to be senescence regulated. We selected 39 candidate genes and confirmed their time-dependent response to enhanced ANAC092 expression by quantitative RT-PCR. We also found that the majority of them (24 genes) is up-regulated by salt stress, a major promoter of plant senescence, in a manner similar to that of ANAC092 which itself is salt-responsive. Furthermore, 24 genes like ANAC092 turned out to be stage-dependently expressed during seed growth with marginal expression at early and elevated expression at late stages of seed development. Disruption of ANAC092 increased the rate of seed germination under saline conditions, whereas the opposite occurred in respective overexpression plants. We also detected a delay of salinity induced chlorophyll loss in detached anac092-1 mutant leaves. Promoter-reporter (GUS) studies revealed transcriptional control of ANAC092 expression during leaf and flower aging and in response to salt stress. We conclude that ANAC092 exerts its functions during senescence and seed germination through partially overlapping gene sets.